Pengembangan Media Edukasi Wisata Lebah Kampoeng Madu Kediri Berbasis Augmented Reality - Muhammad Ariel Naafi'; Faisal Reza Pradhana; Triana Harmini (Prosiding, 2025)
This study aims to develop a bee tourism educational media using Augmented Reality at KampungMadu Kediri to deliver information interactively and comprehensibly. The development method employed the System Development Life Cycle with the Waterfall model through stages of analysis, design, implementation, and testing. The Android-based application displays 3D objects, text, and educational audio by scanning visual markers. Blackbox Testing results showed that all features functioned as expected. The educational material evaluation recorded an average score of 4.2 (close to “Strongly Agree”) or 84%, categorized as “Very Good,” indicating relevant, accurate, and engaging content. These findings demonstrate that the application is effective in improving visitor literacy, enhancing the tourism experience, and functioning without the need for a direct guide.